CRAFTMANSHIP DALAM PENCIPTAAN POSTER FILM FIKSI ILMIAH â€œTENGKORAKâ€ - Fuadi, Yusron (DeKaVe, 2020)
Science fiction is a rare film genre in Indonesia. Indonesian audience do watches science fiction in cinema, but Indonesian production house seems to be less than eager to make as such. Tengkorak is an independent science fiction designed with all the good intention to break those genre barrier.Film poster is a compulsory byproduct of a feature film. It was made to market the film and to be placed mainly in cinema. The nature of independent production of Tengkorak made it impossible to simply put popular face of a-list Indonesian actors. The inspiration of Tengkorak, which is 1980s science fiction, open up an opportuniy to explore design possibilities, to make it distinctive and memorable.